استخدام قاموس التعبير الخاص والأسلوب المعاصر في تطوير التعبير الشفهي عند الطلبة بمعهد دار الحسنة السنكيلي - Ridha, Muhammad; Muslim, Buhori; Susanti, Susanti (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2021)
The Problems Found by the author when conducting Observation are Darul hasanah Islamic Boarding School students feel bored when hey’re learning Arabic, and they’re also less responsive. Because, Arabic learning doesn’t use additional book to support learning and doesn’t use methods and media that are suitable with the subject being studied. The purpose of this study was to determin the responses of students in the use of dictionaries in learning to speak (kalam) and to determin the process of developing speaking skills using the “al-ta’bir al-khas wa uslub al-ma’ashir” dictionary. This study is an experimental researcher with a design one grup pree- post test design and to collect research data using direct observation sheets and tests before conducting experiments and after. And as for the population in this study was only some students, namely class 2 Mas students, totaling 34 students The results obtained from the teacher and students observation sheets during the learning process obtained very good scores with the results (teacher observation 82,5 % and student observations 85 % ). And the results of the pre-test post-test obtained a significant level (2- tailed) 0,000< 0,05 after the T test using the “SPSS” program indicates that the hypothesis (Ha) is accepted and the hypotesis (Ho) is rejected. This show that learning to speak (kalam) using a dictionary can develop students’ ability to speak arabic.